2023
DOI: 10.4251/wjgo.v15.i1.36
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine for transformation of gastric precancerous lesions to gastric cancer: A critical review

Abstract: Gastric cancer (GC) is a common gastrointestinal tumor. Gastric precancerous lesions (GPL) are the last pathological stage before normal gastric mucosa transforms into GC. However, preventing the transformation from GPL to GC remains a challenge. Traditional Chinese medicine (TCM) has been used to treat gastric disease for millennia. A series of TCM formulas and active compounds have shown therapeutic effects in both GC and GPL. This article reviews recent progress on the herbal drugs and pharmacological mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…Using “hawthorn” as a search term, we conducted a search on the special food query platform ( http://ypzsx.gsxt.gov.cn/specialfood/#/food ) of China’s State Administration of Market Regulation and discovered that health products predominantly formulated with hawthorn in combination with other traditional Chinese medicinal ingredients possessing both nutritional and health-promoting functions, while also showcasing the potential for cancer prevention. This is specifically evident in three aspects: first, enhancing immunity to maintain or improve overall health ( Yang et al, 2024 ); Second, assisting in protecting gastric mucosa, inhibiting damage to gastric mucosa, and reducing the risk of gastric cancer development ( Wang H. et al, 2020 ; Păun et al, 2020 ; Xu W. et al, 2022 ; Yi et al, 2022 ; Zhong et al, 2023 ); Third, aiding in protecting against chemical-induced liver damage, reducing the hepatotoxicity of chemical products, and thereby decreasing the incidence of liver cancer ( Han et al, 2020 ; Atia et al, 2022 ). Relevant health products are illustrated in Table 1 , indicating that strengthening the application of such health products has a positive effect on cancer prevention.…”
Section: The Health Value Of Hawthorn: Cancer Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using “hawthorn” as a search term, we conducted a search on the special food query platform ( http://ypzsx.gsxt.gov.cn/specialfood/#/food ) of China’s State Administration of Market Regulation and discovered that health products predominantly formulated with hawthorn in combination with other traditional Chinese medicinal ingredients possessing both nutritional and health-promoting functions, while also showcasing the potential for cancer prevention. This is specifically evident in three aspects: first, enhancing immunity to maintain or improve overall health ( Yang et al, 2024 ); Second, assisting in protecting gastric mucosa, inhibiting damage to gastric mucosa, and reducing the risk of gastric cancer development ( Wang H. et al, 2020 ; Păun et al, 2020 ; Xu W. et al, 2022 ; Yi et al, 2022 ; Zhong et al, 2023 ); Third, aiding in protecting against chemical-induced liver damage, reducing the hepatotoxicity of chemical products, and thereby decreasing the incidence of liver cancer ( Han et al, 2020 ; Atia et al, 2022 ). Relevant health products are illustrated in Table 1 , indicating that strengthening the application of such health products has a positive effect on cancer prevention.…”
Section: The Health Value Of Hawthorn: Cancer Preventionmentioning
confidence: 99%
“…Medicinal and edible Chinese medicines are essential components of TCM ( Chen, 2023 ), combining the concepts of food and medicine to create a unique treatment and diet regimen that aims to harmonize the yin and yang balance in the body. These medicines offer numerous benefits, including high safety levels, minimal side effects, flexible dosage forms, good patient compliance, and the ability to target precancerous lesions ( Hou and Jiang, 2013 ; Jiang et al, 2023 ; Zhong et al, 2023 ). Recent studies have confirmed the anticancer properties of extracts and purified bioactive monomer components present in various medicinal and edible Chinese medicines ( Huang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese Medicine (TCM) has been proven to have certain advantages in the treatment of Ivyspring International Publisher PLGC [8]. Classical Chinese medicine formulas and some herbal chemical components have been used to treat PLGC, which can carry out multi-pathway and multi-target comprehensive intervention [9].…”
Section: Introductionmentioning
confidence: 99%
“…There are many interventions for CINV, which can be generally categorized into pharmacologic and nonpharmacologic interventions. Many recent studies have shown that laughter yoga, [9] ginger, [10,11] acupuncture, [12] music therapy, [13] dietary interventions, [14] etc combined or noncombined antiemetics can alleviate CINV to varying degrees. It can be seen that CINV can be intervened by exercise, Chinese medicine, music, and diet in combination with antiemetic drugs.…”
Section: Introductionmentioning
confidence: 99%